2018
DOI: 10.1186/s11658-018-0077-1
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α promotes the migration and invasion of hepatocellular carcinoma cells via the IL-8–NF-κB axis

Abstract: BackgroundHypoxia plays a critical role in many cancers. Hypoxia inducible factor-1α (HIF-1α) is an important mediator of the hypoxia response. It regulates the expression of various chemokines involved in tumor growth, angiogenesis and metastasis but the associated pathway needs further investigation.MethodsThe expression level of HIF-1α was determined in hepatocellular carcinoma (HCC) cells. The correlation of interleukin-8 (IL-8) and HIF-1α was assessed by knocking down HIF-1α. These cells were also used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 40 publications
(32 reference statements)
5
26
0
Order By: Relevance
“…However, it has not been clarified whether these two pathways are activated by related regulatory mechanisms in HCC. Interestingly, consistent with our previous findings on Nogo‐B, knockdown of HIF‐1 or AP‐1 was also reported to attenuate proliferation, migration, and invasion of HCC cells 53,54 . As most of the angiogenic factors, including VEGF, are induced by a hypoxic TME, we first examined the association between Nogo‐B expression and hypoxic conditions.…”
Section: Discussionsupporting
confidence: 72%
“…However, it has not been clarified whether these two pathways are activated by related regulatory mechanisms in HCC. Interestingly, consistent with our previous findings on Nogo‐B, knockdown of HIF‐1 or AP‐1 was also reported to attenuate proliferation, migration, and invasion of HCC cells 53,54 . As most of the angiogenic factors, including VEGF, are induced by a hypoxic TME, we first examined the association between Nogo‐B expression and hypoxic conditions.…”
Section: Discussionsupporting
confidence: 72%
“…In contrast, in some bladder cancer lines, it is associated with the activation of NF-κB but not AP-1 [ 185 ]. In turn, in hepatocellular carcinoma cells, an increase in the expression of CXCL8 in chronic hypoxia is dependent on the activation of HIF-1 and the effect of this transcription factor on NF-κB [ 186 , 187 ]. In other types of cancer, the effect of HIF-1 may differ—for example, in colon cancer cells, chronic hypoxia increases the expression of CXCL8 via NF-κB [ 188 ].…”
Section: Ligands Of Receptors Cxcr1 and Cxcr2mentioning
confidence: 99%
“…Tumor hypoxia is one of the main reasons for chemoradiotherapeutic resistance, which affects tumor invasiveness and poor prognosis [162]. HIF1A is a transcription factor with critical functions in the hypoxia response by induction of metastasis and angiogenesis [163][164][165]. It was reported that there was miR-338-3p downregulation in BC tissue and cells.…”
Section: Transcription Factors and Regulatorsmentioning
confidence: 99%